ANALISIS KINERJA BANK PEREKONOMIAN RAKYAT (BPR) SEBELUM DAN SETELAH BERKOLABORASI DENGAN INOVASI FINTECH LENDING DAN FUNDING - Desy Amelia; Masyhuri Hamidi; Fajri Adrianto (Journal Publicuho, 2025)
This study analyses the financial performance of Rural Economic Banks (BPR) before and after collaboration with financial technology (fintech) innovations in lending and funding through Komunal Group, the pioneer of BPR digitalisation in Indonesia. The observation period is divided into two phases: before collaboration (2019–2021) and after collaboration (2022–2024). The study aims to examine the influence of financial variables such as Cash Ratio (CR), Loan to Deposit Ratio (LDR), Non-Performing Loan (NPL), and Operating Expenses to Operating Income Ratio (BOPO) on Return on Assets (ROA) of BPR, as well as to compare financial performance between the two periods. The method used is panel data regression with a Random Effect Model, accompanied by tests for normality, heteroscedasticity, multicollinearity, and autocorrelation. The sample consists of 14 BPRs. The results show no significant difference in ROA between the two periods. However, LDR significantly increased and NPL significantly decreased after collaboration, indicating improved credit distribution and asset quality. CR decreased, although not statistically significant, reflecting a shift in liquid assets toward credit expansion through fintech. BOPO consistently has a significant negative effect on ROA in both periods, emphasising the importance of operational efficiency. This study also highlights the need for adaptive liquidity management and good governance to maintain optimal financial performance.